2020
DOI: 10.1111/jav.02472
|View full text |Cite
|
Sign up to set email alerts
|

Host sex and age typically explain variation in parasitism of rock ptarmigan: implications for identifying determinants of exposure and susceptibility

Abstract: Measures of parasitism often differ between hosts. This variation is thought due in part to age or sex differences in exposure to parasites and/or susceptibility to parasitism. We assessed how often age or sex biases in parasitism were found using a large, multiyear (2006-2017) dataset of 12 parasite species of Icelandic rock ptarmigan (Lagopus muta). We found host traits (i.e. age and/or sex) accounted for significant variation in abundance of 11 of the 12 parasite species. We often found increased abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Summarizing the competing best models (Table 1) showed that host age explained variation in abundance of T. tenuis with adults having more worms than juveniles; those patterns agree with Nielsen et al. 2020. Thus, inclusion of two potential predictor parasites did not change host age– T. tenuis relations.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Summarizing the competing best models (Table 1) showed that host age explained variation in abundance of T. tenuis with adults having more worms than juveniles; those patterns agree with Nielsen et al. 2020. Thus, inclusion of two potential predictor parasites did not change host age– T. tenuis relations.…”
Section: Resultssupporting
confidence: 83%
“…Hereafter, we are referring specifically to previous results of Nielsen et al. (2020) whenever current results are compared to previously established patterns with respect to host traits. These same effects of host traits were seen in three of four best models including three potential predictor parasites; age, but not the age:sex interaction, was also significant in the fourth best model (Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations